Associations Between Provider Designation and Female-specific Cancer Screening in Women Veterans. Issue 4 (April 2015) - Bean-Mayberry, Bevanne; Bastian, Lori; Trentalange, Mark; Murphy, Terrence E.; Skanderson, Melissa; Allore, Heather; Reyes-Harvey, Evelyn; Maisel, Natalya C.; Gaetano, Vera; Wright, Steven; Haskell, Sally; Brandt, Cynthia
Abstract : Background: In 2010, the Department of Veterans Affairs Healthcare System (VA) implemented policy to provide Comprehensive Primary Care (for acute, chronic, and female-specific care) from designated Women's Health providers (DWHPs) at all VA sites. However, since that time no comparisons of quality measures have been available to assess the level of care for women Veterans assigned to these providers. Objectives: To evaluate the associations between cervical and breast cancer screening rates among age-appropriate women Veterans and designation of primary-care provider (DWHP vs. non-DWHP). Research Design: Cross-sectional analyses using the fiscal year 2012 data on VA women's health providers, administrative files, and patient-specific quality measures. Subjects: The sample included 37, 128 women Veterans aged 21 through 69 years. Measures: Variables included patient demographic and clinical factors (ie, age, race, ethnicity, mental health diagnoses, obesity, and site), and provider factors (ie, DWHP status, sex, and panel size). Screening measures were defined by age-appropriate subgroups using VA national guidelines. Results: Female-specific cancer screening rates were higher among patients assigned to DWHPs (cervical cytology 94.4% vs. 91.9%, P <0.0001; mammography 86.3% vs. 83.3%, P <0.0001). In multivariable models with adjustment for patient and provider characteristics, patients assigned to DWHPs had higher odds of cervical cancer screening (odds ratio, 1.26; 95% confidence interval, 1.07–1.47; P <0.0001) and breast cancer screening (odds ratio, 1.24; 95% CI, 1.10–1.39; P <0.0001). Conclusions: As the proportion of women Veterans increases, assignment to DWHPs may raise rate of female-specific cancer screening within VA. Separate evaluation of sex neutral measures is needed to determine whether other measures accrue benefits for patients with DWHPs.